RUSSIAN HISTORIOGRAPHY OF THE TURN OF 20TH – 21ST CENTURIES ABOUT THE 1932  1933 FAMINE IN THE USSR - M. V. Kazmina (Вестник Кемеровского государственного университета, 2014)
The paper analyzes the main points of view expressed in the Russian historiography about the causes, prevalence and consequences of the famine in 1932 – 1933.